2017
DOI: 10.1364/ol.42.000627
|View full text |Cite
|
Sign up to set email alerts
|

Soliton-mediated orientational ordering of gold nanorods and birefringence in plasmonic suspensions

Abstract: We report on the soliton-mediated orientational ordering of gold nanorods in a colloidal plasmonic suspension. Due to the nonlinear optical response of the suspension, a light beam forms an optical spatial soliton which creates an effective optical waveguide. The orientation of the nanorods along the waveguide is regulated by the optical torque exerted by the linearly polarized soliton beam. By measuring the polarization transmission spectrum of a probe beam at a wavelength far from the plasmonic resonance, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Assuming that Imn x − Imn y becomes 3 times smaller than in the fully ordered case, and ordering only occurs over an action length of 500 μm (50 times the beam radius at the focus), we find the percentage difference between the perpendicular and parallel transmittances will be within 2%, a result consistently observed in our experiments. We want to point out that the conclusion drawn here does not match with that from our previous report [35], where an aqueous suspension of gold nanorods was pumped by a 532 nm laser beam and the polarization-dependent transmission of a probe beam appeared to be identified. After a careful examination of the previous results and a series of new experiments performed in the same setting, we found that the apparent polarization-dependent transmission was observed in experiments where the power of the probe beam input to the sample was not fixed when its polarization was adjusted with polarization optics.…”
Section: E Soliton-mediated Anisotropic Optical Propertycontrasting
confidence: 93%
See 1 more Smart Citation
“…Assuming that Imn x − Imn y becomes 3 times smaller than in the fully ordered case, and ordering only occurs over an action length of 500 μm (50 times the beam radius at the focus), we find the percentage difference between the perpendicular and parallel transmittances will be within 2%, a result consistently observed in our experiments. We want to point out that the conclusion drawn here does not match with that from our previous report [35], where an aqueous suspension of gold nanorods was pumped by a 532 nm laser beam and the polarization-dependent transmission of a probe beam appeared to be identified. After a careful examination of the previous results and a series of new experiments performed in the same setting, we found that the apparent polarization-dependent transmission was observed in experiments where the power of the probe beam input to the sample was not fixed when its polarization was adjusted with polarization optics.…”
Section: E Soliton-mediated Anisotropic Optical Propertycontrasting
confidence: 93%
“…While ordering of an ensemble of rods has been demonstrated with techniques including applying electric fields [15][16][17][18][19][20], self-assembly based fabrication [21][22][23], the stretched-film method [24][25][26], and the electrospinning technique [27,28], so far only manipulation of individual plasmonic nanorods was demonstrated experimentally with optical traps [29][30][31][32][33][34]. Recently, we attempted to achieve orientational ordering of gold nanorods inside an optical soliton channel established by pumping a colloidal suspension of gold nanorods with a 532 nm laser beam [35]. In the study, transmission as a function of the polarization direction of a linearly polarized low-intensity 1064 nm probe beam was measured, providing indirect evidence for the presence of nanorod ordering in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear self-trapping of laser light in soft-matter systems, such as dielectric [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ] or plasmonic colloids [ 6 ], [ 7 ], [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ] as well as biological media [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], has attracted increased attention over the past decade. The effect is described as diffraction-less propagation of laser light, trapped over many diffraction lengths by virtue of the intensity-dependent nonlinear refractive index of the medium.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of plasmonic nanocolloids, several studies have reported that self-trapping of laser light is possible by virtue of particle concentration gradients arising from the enhanced particle polarizabilities and exerted on them optical forces [ 7 , 8 , 10 , 14 , 15 ]. Others have demonstrated in the same context that the beam is not self-trapped; in fact, a self-channeling effect (a phenomenological self-trapping) is observed because of nonlinear thermal lensing, giving the impression of a self-trapped beam, particularly when the laser field is tuned near the plasmon resonance [ 6 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%